O impacto na autonomia dos idosos que pararam de dirigir - Domenico, Caetano Munhoz De (2011)
The social health of elderly is directly linked to its independence and autonomy on their activities. The act of driving involves autonomy and independence to make decisions and often, when elderly stop or decreases driving, it will impaired their social health. The study aimed to identify the impact on autonomy of elderly who have lost their Driver's License or stop driving for any reason. We selected seven (07) elderly of both sexes, over 65 years and had suspended driver's license. Semi-structured interviews were carried, where the subjects answered a questionnaire with five pre-determined questions. Then, the participants underwent detailed clinical anamnesis and neuropsychiatric evaluation to assess their cognitive state. The tests applied were: Cambridge Cognitive Examination (CAMCOG) (ROTH et. al., 1986), the Mini-Mental State Examination (MMSE) (FOLSTEIN et. al., 1975), the Clock Drawing Test (CDT) according to the scale Clock Drawing Interpretation Scale (MENDEZ et. al. 1992; SHULMAN et. al., 1993), the Geriatric Depression Scale (GDS) with 15 short items (YESAVAGE et. al., 1983), Scale Depression of the CAMDEX (Roth et. al., 1986) and the Functional Activities Questionnaire Pfeffer (PFEFFER et. al., 1982). The results showed that all the elderly who had lost Driver's License, stopped driving for any other reason or had a decrease in driving, experienced, in more than a half of cases, decrease on leisure activities and scored for symptoms of depression. It can be concluded that among those elders that rely on their cars as the most important transportation, mobilization and socialization way, there was a impaired quality of life due decrease on independency and autonomy